Characterization of a Novel L-Asparaginase from Mycobacterium gordonae with Acrylamide Mitigation Potential - Huibing Chi (MDPI AG, 2021)
L-asparaginase (E.C.3.5.1.1) is a well-known agent that prevents the formation of acrylamide both in the food industry and against childhood acute lymphoblastic leukemia in clinical settings. The disadvantages of L-asparaginase, which restrict its industrial application, include its narrow range of pH stability and low thermostability. In this study, a novel L-asparaginase from Mycobacterium gordonae (GmASNase) was cloned and expressed in Escherichia coli BL21 (DE3). GmASNase was found to be a tetramer with a monomeric size of 32 kDa, sharing only 32% structural identity with Helicobacter pylori L-asparaginases in the Protein Data Bank database. The purified GmASNase had the highest specific activity of 486.65 IU mg−1 at pH 9.0 and 50 °C. In addition, GmASNase possessed superior properties in terms of stability at a wide pH range of 5.0–11.0 and activity at temperatures below 40 °C. Moreover, GmASNase displayed high substrate specificity towards L-asparagine with Km, kcat, and kcat/Km values of 6.025 mM, 11,864.71 min−1 and 1969.25 mM−1min−1, respectively. To evaluate its ability to mitigate acrylamide, GmASNase was used to treat potato chips prior to frying, where the acrylamide content decreased by 65.09% compared with the untreated control. These results suggest that GmASNase is a potential candidate for applications in the food industry.